2005
DOI: 10.1093/poq/nfi004
|View full text |Cite
|
Sign up to set email alerts
|

Playing the Race Card in the Post-Willie Horton Era: The Impact of Racialized Code Words on Support for Punitive Crime Policy

Abstract: To date, little is known about the precise impact of racially coded words and phrases. Instead, most of what we know about racialized messages comes from studies that focus on pictorial racial cues (for example, the infamous "Willie Horton" ad) or on messages with an extensive textual narrative that is laced with implicit racial cues. Because in a "post-Horton" era strategic use of racially coded words will often be far more subtle than those explored in past studies, we investigate the power of a single phras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
166
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(174 citation statements)
references
References 11 publications
6
166
0
2
Order By: Relevance
“…Such triggers may be subtle cues in the news, such as words with a racial connotation, such as "innercity" (Domke, 2001;Hurwitz & Peffley, 2005) or mug shots of members of racial minorities (Dixon & Maddox, 2005;Gilliam & Iyengar, 2000). In addition, negative depictions of minorities also function as triggers of stereotype and prejudice activation.…”
Section: Experimental Evidence Of Media Effects On Racial Attitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…Such triggers may be subtle cues in the news, such as words with a racial connotation, such as "innercity" (Domke, 2001;Hurwitz & Peffley, 2005) or mug shots of members of racial minorities (Dixon & Maddox, 2005;Gilliam & Iyengar, 2000). In addition, negative depictions of minorities also function as triggers of stereotype and prejudice activation.…”
Section: Experimental Evidence Of Media Effects On Racial Attitudesmentioning
confidence: 99%
“…Playing the race card is a common strategy to mobilize voters in elections (Boomgarden & Vliegenthart, 2007;Hurwitz & Peffley, 2005;Valentino, 1999). Third, in order to demonstrate media effects the study relies on media content that news users are exposed to instead of measures of media exposure as a predictor of racial attitudes.…”
Section: News Media Influence On Stereotypic Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…Horwitz and Peffley (2005) randomly assigned subjects to two groups, with one group being asked question A below, and one group being asked question B (difference underlined by me, from 102-3). This small change-the addition of 'inner city'-turned out to have a significant effect on the answer that subjects gave, but the nature of this effect was strongly influenced by subjects' pre-existing racial attitudes.…”
Section: 'Inner City'mentioning
confidence: 99%
“…8 A related study adds additional support to the claim that "inner city" conveys something about African Americans. Hurwitz & Peffley 2005 showed that the mere insertion of "inner city" in a question about spending money on prisons on antipoverty programs was sufficient to make participants' racial prejudice against African Americans more predictive of higher support for government spending on prisons. Their question was (p. 102-3):…”
Section: Fixing Ideas: Some Effects Of Code Wordsmentioning
confidence: 99%